Operational practices for garment industry of Esquire Knit Composite Ltd. - Gone, Md. Osman (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2021.